The spread of the progressive and its ‘future’ use - Nesselhauf, Nadja (English language and linguistics, 2007)
Numerous factors have been identified as being relevant to the spread of the progressive in Late Modern English. The potential role of the ‘future’ use of the construction (as in I'm flying home next week) has, however, been neglected so far. The present study aims to fill this gap by providing a comprehensive analysis of the development of the progressive with future time reference since 1750 in British English. The investigation focuses on the question of whether and to what degree the factors at work in the development of the construction coincide with factors relevant to the development of other types of progressives.The analysis demonstrates that the ‘future’ use of the progressive does indeed play a part in the spread of the progressive. Several hitherto unknown factors special to the development of the ‘future’ use of the progressive are also uncovered, among them an increased (and possibly) new use of the construction to express spontaneous decisions.